Analysis of the Earth-Moon Lagrange points for improving GNSS performance in lunar space - Cormier, Luis (2023)
This thesis discusses the potential use of the Earth-Moon Lagrange points for improving global navigation satellite system (GNSS) signal availability and distribution on Lunar missions. The Lagrange points are points of equilibrium which occur when modelling the Earth and Moon under the circular restricted three body problem (CR3BP), and represent interesting yet sparsely research potential for Lunar missions. A review of key literature is presented in this thesis, followed by the methodology taken throughout this research. From this, the key results are presented and implications discussed, as well as factors which could affect its practical roll-out on a real-world mission.